KONTRAK JUAL BELI DI ERA KONTEMPORER - Lukman Hamdani (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2019)
Buying and selling contracts are very essential in terms of commerce because they are related to the validity of buying and selling, Khiyar, Bai ’Al-Mu’atha, the attitude of Ant-Tharadin and as-saman and as-si’r. Because buying and selling things like this must be clear and detailed so that no one is disappointed between buyers and sellers, the most common problem is not understanding and understanding the essence of the sale and purchase contract itself even though this is very necessary and needed in terms of commerce .